2011
DOI: 10.2169/internalmedicine.50.4617
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ulcers as an Initial Manifestation of Systemic Lupus Erythematosus

Abstract: Digital ulcers (DUs) and gangrene are common skin manifestations of connective tissue diseases, especially systemic sclerosis. Raynaud's phenomenon (RP) is an almost universal manifestation of systemic sclerosis, with 95% of all patients being affected, and resulting in DUs in approximately 30% of the patients each year. Although RP may be present in approximately 25-50% of the patients, DUs are relatively rare in systemic lupus erythematosus (SLE) and never present as an initial manifestation of disease. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
(12 reference statements)
0
15
0
2
Order By: Relevance
“…In their study that was conducted in 1962, Dubois and Arterberry found that the latent period between diagnosing SLE and developing digital gangrene was from 1 to 18 years [2]. Rosato et al claimed that acute digital gangrene is never the first presentation of SLE [6]. Our patient's presentation is not only rare but also goes against the usual picture of SLE for she did not show any prior features of SLE.…”
Section: Discussionmentioning
confidence: 55%
“…In their study that was conducted in 1962, Dubois and Arterberry found that the latent period between diagnosing SLE and developing digital gangrene was from 1 to 18 years [2]. Rosato et al claimed that acute digital gangrene is never the first presentation of SLE [6]. Our patient's presentation is not only rare but also goes against the usual picture of SLE for she did not show any prior features of SLE.…”
Section: Discussionmentioning
confidence: 55%
“…There have been fewer reports of digital gangrene as initial manifestation of SLE. Rosato et al 12 had even asserted that digital ulcers and gangrene are never present as initial manifestation in SLE. However, Yang et al 13 had reported a case of acute gangrene of finger in an 8-year-old Korean girl without prior features of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…3 Digital ulcers and gangrene are common skin manifestations of active systemic connective tissue diseases although they are relatively rare in systemic lupus erythematosus. 4 Additionally, It is rather common in SLE patients to present with generalized lymphadenopathy, hepatosplenomegaly fever and many was transferred to fever hospital as fever of unknown origin. In this challenging situation, it is very important to exclude hematological malignancies (Leukemias/ lymphomas), that is why lymph node biopsy and bone marrow examination were essential.…”
Section: Discussionmentioning
confidence: 99%
“…Retics 5.1%, Coomb's test: negative, ESR: 120 mm, CRP 6 mg%. Blood chemistry; AST: 33 IU/ L, ALT: 283 IU/ L, Total proteins: 7.6 g/dl, Albumin: 2.6 g/dl Case Report (low), LDH: 690 IU/L, s.creatinine 0.5 mg/dl, Fasting blood sugar 98 mg/dl, Total bilirubin 0.9 mg/dl Urine analysis: albumin +ve, protein/creatinine (P/C) ratio: 0 4. ANA was positive with homogenous and rim pattern, DNA positive, HCV Ab: Positive, C-ANCA negative, P-ANCA: Positive.…”
mentioning
confidence: 96%